Making supercapacitor carbon electrodes from lemongrass leaf biomass with variations in physical activation temperature - Jaliaz, Akmal; Awitdrus, Awitdrus (Indonesian Physics Communication, 2025)
Supercapacitor is energy storage device consisting of current collector, electrodes, separator, and electrolyte. Material selection and fabrication of the electrodes play an important role in improving the performance of the supercapacitor. In this research, carbon electrodes of supercapacitors were made from citronella leaves using variations in physical activation temperature. The preparation of carbon electrodes were starts from the pre-carbonization at temperature of 200℃ for 2 hours, chemical activation using 0.3 M KOH as activating agent, carbonization process using N2 gas at temperature of 600℃ and physical activation using CO2 gas with temperature variations of 750℃, 800℃, and 850℃. The highest of percentage density reduction at temperature 800℃ is 51.42%. Analysis using X-ray diffraction showed that the sample has a semicrystalline structure with the highest of ratio Lc/La and average number of microcrystalline layer (Np) at temperature of 800℃, are 0.27 and 1.67 respectively. The highest of specific capacitance value is 122 F/g at temperature 800℃. The result show that the optimum physical activation temperature for carbon electrodes based on citronella leaves is 800℃.